Regional maps of occupational heat exposure: past, present, and potential future - Tord Kjellstrom; Bruno Lemke; Olivia M. Hyatt (Taylor & Francis Group, 2010)
Background: An important feature of climate change is increasing human heat exposure in workplaces without cooling systems in tropical and subtropical countries. Detailed gridded heat exposure maps will provide essential information for public health authorities. Objectives: To develop and test methods for calculating occupational heat exposures and present results in easily interpreted maps. Design: Published formulas for a common occupational heat exposure index, the WBGT (Wet Bulb Globe Temperature), were used in combination with global gridded climate data to calculate heat exposure in 0.58 grid squares. Monthly averages of daily maximum temperatures, as indicators of typical temperatures during the hottest part of the day, and corresponding water vapour pressures produced estimates of monthly WBGT indoors (without cooling systems) or outdoors in the shade. Results: The maps show the WBGT within four hot regions of the world during the three hottest months in 1975 and 2000: Australia, South Asia, Southern Africa, Central America, and southern US. Between 1975 and 2000 a WBGT increase of 0.5–1°C was common and the maps show clear decreases in some places. The time trends fit with the development of global climate change. The high WBGT values (particularly in South Asia) already cause excessive occupational heat exposures during the three hottest months. If continued climate change increases WBGT by 3°C, our maps identify areas where occupational heat stress in non-cooled workplaces will be extreme. Conclusions: The mapping method provides a rapid visual impression of occupational heat exposures in large regions of the world. The local changes in WBGT between 1975 and 2000 fit with the global climate change trends. Future increases of WBGT may create extreme heat exposure situations in large areas of the world.